Effect of cellulose nanocrystal-stabilized cinnamon essential oil Pickering emulsions on structure and properties of chitosan composite films - Liu, Jian; Song, Feixiang; Chen, Runyi; Deng, Guitang; Chao, Yanxia; Yang, Zhuohong; Wu, Hong; Bai, Mei; Zhang, Peng; Hu, Yang (Carbohydrate polymers, 2022)
The low water-resistance and limited antibacterial activity of chitosan (CS) film hinder its practical applications in food preservation field. To solve these issues, we have facilely and effectively fabricated cinnamon essential oil (CEO)-loaded composite films via incorporating cellulose nanocrystal (CNC)-stabilized CEO Pickering emulsions into CS-based film-forming matrix. Research results show the well distribution of emulsion droplets in film matrix. The insertion of CEO emulsions can improve film water-resistance and antibacterial activity, but reduces its mechanical strength. Concretely, the water contact angle and inhibition zone of composite films can increase by about 12.3° and 2 times compared with CS control film. Compared with tween-80, CNCs can increase film tensile strength by about 3.52 MPa and observably offset the decline of film mechanical property by CEO. Moreover, the film prepared with 3 w/v% CNC stabilized 30 v/v% CEO Pickering emulsion not only enhances pork preservation, but also maintain its structural stability. The fabricated antimicrobial films have considerable potential for packaging application. [Display omitted] •Cinnamon essential oil (CEO) was loaded into Pickering emulsion templates.•CEO-loaded cellulose nanocrystals (CNCs)/chitosan composite film was prepared.•Pickering emulsion was templated and evenly distributed in film-forming matrix.•CNCs can offset the decline of film mechanical property causing by addition of CEO.•Composite films show controllable release property and good antibacterial activity.